IMPROVING STUDENTS WRITING SKILL BY USING FREE WRITING TECHNIQUE - Mustakim Sagita Jamaliah (Universitas Jabal Ghafur, 2020)
The aimed of this research is to find out does the use of free writing technique improve students’ writing skill or not. The research conducted at SMPN 1 Kembang Tanjong with experimental research design. The population was all of the eighth grade students with the total number of students were 106. The sample was class VIII 1 as experimental class and VIII 2 as control class. The instrument used in pre-test and post-test was a set of written test. Rubric scoring system by Heaton used to analyze the students writing score and independent T-test used to analyze the data. The result of data analysis showed that in pre-test the students at experimental class got mean score 53,5 while at control class got 52,10. In post-test, the students at experimental class who taught writing by using free writing technique got a mean score 78,08 and at control class students who was not got the treatment as in experimental class only got a mean score 57,70. The result of independent T-test, at pretest t-count ? t-table (0,154 ? 1,685) and P-value ? level of significance (0,879 ? 0,05) it means there were no significantly differences between experimental class and control class at pre-test and at posttest t-count ? t-table (3.845 ? 1,685) and P-value ? level of significance (0,00 ? 0,05) it means teaching writing by using free writing technique improve significantly the students writing skill. So, the hypothesis was accepted. Key Words: Writing, Free Writing, Descriptive Text